2018
DOI: 10.1128/jcm.02045-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Detection Limits of Fourth- and Fifth-Generation Combination HIV Antigen-Antibody, p24 Antigen, and Viral Load Assays on Diverse HIV Isolates

Abstract: Detection of acute HIV infection is critical for HIV public health and diagnostics. Clinical fourth-generation antigen (Ag)/antibody (Ab) combination (combo) and p24 Ag immunoassays have enhanced detection of acute infection compared to Ab-alone assays but require ongoing evaluation with currently circulating diverse subtypes. Genetically and geographically diverse HIV clinical isolates were used to assess clinical HIV diagnostic, blood screening, and next-generation assays. Three-hundred-member panels of 20 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 28 publications
2
30
0
1
Order By: Relevance
“…The limit of detection of the p24 Ag by these assays ranged from 2 to 7 pg, which corresponds to 4.4 to 4.9 log copies of RNA per ml. The assays detect HIV infection from 7 to 11 days earlier than the anti-HIV IgM/IgG immunoassays (32)(33)(34)(35). In our study, the results of the BRC, ARC, and BPX assays from samples collected at 24 weeks after the initiation of ART in AHI also showed generally good agreement at S/CO results below 10.…”
Section: Discussionsupporting
confidence: 62%
“…The limit of detection of the p24 Ag by these assays ranged from 2 to 7 pg, which corresponds to 4.4 to 4.9 log copies of RNA per ml. The assays detect HIV infection from 7 to 11 days earlier than the anti-HIV IgM/IgG immunoassays (32)(33)(34)(35). In our study, the results of the BRC, ARC, and BPX assays from samples collected at 24 weeks after the initiation of ART in AHI also showed generally good agreement at S/CO results below 10.…”
Section: Discussionsupporting
confidence: 62%
“…Although two previous studies reported the full HIV-1 genome (including pol ) from a vertically infected 12-month-old baby 54 or gag sequences from 15 children in Kimpese, rural DRC 53 , our study presents the most extensive data regarding HIV-infected children and adolescents in the country. The updated high genetic diversity observed in the DRC also represents a real challenge for future vaccine development and for efficiency of antiretroviral treatment, diagnostic and monitoring tests of HIV infection 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Although viral diversity could affect the limit of detection of serological assays this is more of a concern with molecular assays, as peptides (amino acid sequences) are more conserved than nucleic acid sequences. Primer or probe mismatches with template sequences may result in under‐ quantification or non‐detection in the case of quantitative or qualitative assays, respectively, or in case of genotypic drug resistance assays in failure of amplification or sequencing reactions.…”
Section: Diagnostic Sensitivity and Specificity ‐ Not So Universalmentioning
confidence: 99%
“…In these cases both the screening and confirmation assay could be performed on the wrong patient, unless a separate, independent sample is obtained. Fourth generation HIV‐1 serology assays, in addition to being able to detect antigen, albeit only at relatively high concentration, are often highly sensitive for low level antibody, which enables the detection of early stage (Fiebig 3) antibody positive cases . However, as antibody levels in patients with chronic HIV infection can be very high, microscopic carryover from positive samples could result in false positive results.…”
Section: Confirmation Tests: Independent or Replicating Screening Assmentioning
confidence: 99%